PENGEMBANGAN SISTEM PENGANGGARAN YANG EFEKTIF UNTUK MENINGKATKAN PROFITABILITAS PERUSAHAAN - Feby Salsabila Dasril; Muhammad Abdillah Pratama Aminullah; Risa Adelila Hasibuan; Dini Vientiany (INTERNATIONAL, Journal of Sharia Business Management, 2025)
In the face of increasingly fierce business competition and uncertainty in the global economy, companies need to have an efficient budgeting system to support the achievement of maximum profits. The budgeting system functions not only as a tool for financial planning, but also as a means of controlling and assessing company performance. This study aims to explore the characteristics of an effective budgeting system, the factors that influence budgeting success, and the role of management accounting practices in improving operational efficiency and company profits. The research technique applied is a qualitative approach through systematic literature analysis of various academic journals, reference books, and relevant documents, supported by structured interviews with key informants in the fields of finance and management. The findings reveal that a participatory, adaptive budgeting system based on accurate data and supported by information technology and good management control has a positive impact on operational efficiency, cost control, and increased company profits. Therefore, the development of an integrated and responsive budgeting system is an important factor in increasing company profitability and survival.